Phytosynthesis of Silver Nanoparticles Using Aqueous Leaf Extract of Schleichera oleosa and Their Antioxidant Activity - Retnaningtyas, Yuni; Nafisa, Lia Wardatun; Pangaribowo, Dian Agung (The Journal of Pure and Applied Chemistry Research, 2025)
Silver nanoparticles (AgNPs) have unique properties and biological activity. It was prepared using the phytosynthesis method with an aqueous leaf extract of Schleichera oleosa in which rich of phenolic compounds and can be applied as a bioreductor. Phytosynthesis, environmentally friendly approach that is biocompatible, cost-effective, and predicted can support large-scale synthesis. This paper report total phenol contents, and the phytosynthesis AgNPs, the characterization and evaluation of antioxidative activity. The total phenolic content was determined using the Folin-Ciocalteu method. The optimum AgNPs have a maximum wavelength of 415 nm. FTIR-ATR characterization shows that the functional groups that act as bioreductors and capping agents are phenolic groups. AgNPs have a Z-average value of 78.5 nm with a PDI of 0.382 and have a spherical morphology. Antioxidant activity test using the DPPH method showed IC50 value of AgNPs is 41.837 ± 0.540 µg mL-1 and included a very strong antioxidant.